2020
DOI: 10.1101/2020.11.17.386136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal variations in soil fungal communities and co-occurrence networks along an altitudinal gradient in the cold temperate zone of China: A case study on Oakley Mountain

Abstract: The biogeography of soil fungi has attracted much attention in recent years; however, studies on this topic have mainly focused on mid- and low-altitude regions. The seasonal patterns of soil fungal community structure and diversity along altitudinal gradients under the unique climatic conditions at high latitudes remain unclear, which limits our insight into soil microbial interactions and the mechanisms of community assembly. In this study, Illumina MiSeq sequencing was used to investigate the spatiotemporal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Furthermore, spring consisted of nodes with high BC values (Supplementary Table 15), indicating the importance of the control potential that an individual node exerts over the interactions of other nodes [82]. These complex interactions in spring might consequently enhance system durability and resistance to adverse environmental conditions such as wet-dry and freeze-thaw cycles with changing seasons [83].…”
Section: Soil Microbial Co-occurrence Network Complexity Under Seasonal Successions and In Different Plantationsmentioning
confidence: 99%
“…Furthermore, spring consisted of nodes with high BC values (Supplementary Table 15), indicating the importance of the control potential that an individual node exerts over the interactions of other nodes [82]. These complex interactions in spring might consequently enhance system durability and resistance to adverse environmental conditions such as wet-dry and freeze-thaw cycles with changing seasons [83].…”
Section: Soil Microbial Co-occurrence Network Complexity Under Seasonal Successions and In Different Plantationsmentioning
confidence: 99%
“…Additional work has shown that the vertical distribution patterns of soil fungal communities observed in these studies were usually explained by environmental factors that change along elevation gradients. These include changes s Submission Template mSystems Submission Template mSystems Submission Template mSystems Submission Template mSystems Submission Template mSystems Submission Te 2 in soil moisture and organic carbon at different elevations, resulting in soil fungal diversity and community composition patterns changing with elevation (34,35). The seasonal patterns of soil fungal communities also appear to be inconsistent, according to recent reports.…”
Section: Introduction Tmentioning
confidence: 99%